Simulation Study of Silicon on Insulator MOSFET based inverter for Electric Vehicle Application using MATLAB - Shuhami, Ikhmal Harris; Razali, Muhammad Anas (Evolution in Electrical and Electronic Engineering, 2022)
Silicon-on-insulator (SOI) complementary metal oxide semiconductor (CMOS) technology has matured after beginning as a niche market. The technology first appeared in the early 1980s, with applications in rad-hard (military) and power. SOI structures are made up of a top single-crystal silicon layer that is either separated from the bulk substrate by an insulating layer (such as SiO2) or supported directly by an insulating substrate. The purpose of this paper is to analyse and compare the performance of silicon-on-insulator and silicon-carbide-based inverters. The experimental procedure for obtaining those two semiconductors will be entirely based on MATLAB simulation software. The switching and conduction losses of each semiconductor are used in the comparison. As a result of this paper, SOI outperforms in terms of lowering each loss and the total loss for SOI-based inverter is 3.94 %.